Uma perspetiva externa aos “Tempos de incertezas ou tempos de oportunidades” - Estilita, Joana Berger (Journal of the Portuguese Society of Anesthesiology, 2020)
Editorial: An external perspective to the “times of uncertainty or times of opportunity”